Dynamics of Electronic Word-of-Mouth: Insights from Destination Management Organizations - MEDEKOVÁ, Kristína; POMPUROVÁ, Kristína (Theoretical and Practical Research in Economic Fields, 2024)
This study investigates destination management organizations' (DMOs) perceptions and engagement with electronic word-of-mouth (eWOM) in tourism, aiming to understand its impact on destination management and tourist decision-making. This study adopts a mixed-methods approach, combining qualitative interviews with 46 Slovak and Czech DMOs and quantitative content analysis of eWOM about destinations on popular eWOM platforms - destination websites, Google Maps, and Facebook. The integration of in-depth thematic insights and extensive eWOM data analysis offers a comprehensive understanding of DMO strategies and their effectiveness in eWOM management. While DMO representatives acknowledge the importance of eWOM and claim to actively monitor and respond to it, the content analysis of eWOM reveals a low engagement in terms of the number of reviews and narrative feedback, particularly on destination websites and Google Maps. DMOs appear more active on Facebook, where they engage visitors through contests and respond to reviews and comments, aligning with the interview findings regarding their efforts to manage and respond to eWOM. The discrepancy between the perceived importance of eWOM by DMOs and the actual engagement levels on platforms like Google Maps and destination websites suggests a potential area for improvement in encouraging more narrative feedback and reviews to better manage destination image and visitor experiences. This research contributes to the understanding of eWOM from the supply side by focusing on DMOs' strategies and responses to online tourist feedback, an area previously underexplored in eWOM research within the context of tourism management.